Therapeutic options for extended-spectrum β-lactamases (ESBLs), AmpC β-lactamases producing Escherichia coli and Klebsiella sp. isolated from various clinical samples - Vimal Kumar; Narinder Kaur; Shubham Chauhan; Rosy Bala; Jyoti Chauhan; Harit Kumar; Shivani Devi (Universitas Gadjah Mada, 2022)
Escherichia coli and Klebsiella sp. are the predominant species isolated from clinical samples. Recent and proper understanding of the antibiotic susceptibility pattern of extended-spectrum β-lactamases (ESBL) and AmpC β-lactamases (AmpC) producing E. coli and Klebsiella sp. will prevent the distribution and future incidence of ESBL and AmpC. We designed this study to understand antibiotic susceptibility patterns of ESBL and AmpC producing E. coli and Klebsiella sp. isolated from a tertiary care hospital in North India. A cross-sectional study was conducted from March 2021 to February 2022. Guring this period, various clinical samples were collected and further tested for ESBL producing E. coli and Klebsiella sp. by using the Double disc Synergy test, whereas AmpC was detected by the Boronic acid disk potentiation method. Their antibiotic susceptibility patterns were noted. Various clinical specimens were collected, in which 37.95% were shown growth of bacteria. Among them, 46.67% of E. coli and 25.21% of Klebsiella sp. were identified by standard laboratory protocol. ESBL producing isolates were 44.37% and 34.20% in E. coli and Klebsiella sp., respectively. Whereas AmpC production was detected in 18.27% of E. coli and 29.36% of Klebsiella sp. ESBL and AmpC producing E. coli and Klebsiella sp. isolated from pus, blood, and sputum samples showed the highest sensitivity towards colistin, tigecycline, and imipenem while in urine samples imipenem, meropenem showed the highest sensitivity. Susceptibility patterns of ESBL and AmpC producing E. coli and Klebsiella sp. from various clinical specimens enhance hospital infection management and help clinicians to prescribe the appropriate antibiotics. The carbapenem, nitrofurantoin, colistin and tigecycline were showed highest susceptible against ESBL and AmpC producing E. coli and Klebsiella sp.